Imaging of Leukocyte Trafficking in Alzheimer’s Disease - Pietronigro, Enrica; Zenaro, Elena; Constantin, Gabriela (Frontiers in Immunology, 2016)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder and is characterized by a progressive decline of cognitive functions. The neuropathological features of AD include amyloid beta (Aβ) deposition, intracellular neurofibrillary tangles derived from the cytoskeletal hyperphosphorylated tau protein, amyloid angiopathy, the loss of synapses, and neuronal degeneration. In the last decade, inflammation has emerged as a key feature of AD, but most studies have focused on the role of microglia-driven neuroinflammation mechanisms. A dysfunctional blood–brain barrier (BBB) has also been implicated in the pathogenesis of AD, and several studies have demonstrated that the vascular deposition of Aβ induces the expression of adhesion molecules and alters the expression of tight junction proteins, potentially facilitating the transmigration of circulating leukocytes. Two-photon laser scanning microscopy (TPLSM) has become an indispensable tool to dissect the molecular mechanisms controlling leukocyte trafficking in the central nervous system (CNS). Recent TPLSM studies have shown that vascular deposition of Aβ in the CNS promotes intraluminal neutrophil adhesion and crawling on the brain endothelium, and also that neutrophils extravasate in the parenchyma preferentially in areas with Aβ deposits. These studies have also highlighted a role for LFA-1 integrin in neutrophil accumulation in the CNS of AD-like disease models, revealing that LFA-1 inhibition reduces the corresponding cognitive deficit and AD neuropathology. In this article, we consider how current imaging techniques can help to unravel new inflammation mechanisms in the pathogenesis of AD and identify novel therapeutic strategies to treat the disease by interfering with leukocyte trafficking mechanisms.